2008
DOI: 10.1021/jp800115r
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Light Extraction from SrGa2S4:Eu2+ Film Phosphors Coated with Various Sizes of Polystyrene Nanosphere Monolayers

Abstract: Hexagonally close-packed, two-dimensional (2D), polystyrene (PS) nanosphere photonic crystal (PC) monolayers were coated on sputtered SrGa 2 S 4 :Eu 2+ films using a process involving the self-assembly of PS nanospheres and the simple transfer of the PS nanosphere monolayers to the phosphor surface. The overall aim of this study was to improve the efficiency of light extraction from the phosphor side of the SrGa 2 S 4 : Eu 2+ films. The effects of using PS nanospheres of various diameters (330, 580, and 960 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…As consistent with results in our previous research, 27 the XRD patterns indicate that the as-grown SrGa 2 S 4 :Eu 2þ TFPs annealed at 700 C coincide with the pure orthorhombic PbGa 2 Se 4 phase reported in the corresponding JCPDS cards (Fig. As consistent with results in our previous research, 27 the XRD patterns indicate that the as-grown SrGa 2 S 4 :Eu 2þ TFPs annealed at 700 C coincide with the pure orthorhombic PbGa 2 Se 4 phase reported in the corresponding JCPDS cards (Fig.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…As consistent with results in our previous research, 27 the XRD patterns indicate that the as-grown SrGa 2 S 4 :Eu 2þ TFPs annealed at 700 C coincide with the pure orthorhombic PbGa 2 Se 4 phase reported in the corresponding JCPDS cards (Fig. As consistent with results in our previous research, 27 the XRD patterns indicate that the as-grown SrGa 2 S 4 :Eu 2þ TFPs annealed at 700 C coincide with the pure orthorhombic PbGa 2 Se 4 phase reported in the corresponding JCPDS cards (Fig.…”
Section: Resultssupporting
confidence: 94%
“…For the fabrication of micro-patterned 2D SiO 2 nano-arrays, we used two methods by changing the order of the formation of the micro-and nano-scale patterns. [25][26][27] Furthermore, we demonstrate the micro-patterned emission images of SrGa 2 S 4 :Eu 2þ TFPs by sputtering TFPs on micro-patterned 2D SiO 2 PC nanoarrays. 23 The second approach was to form the micro-scale pattern first and then the nano-scale pattern.…”
mentioning
confidence: 91%
“…Generally, 2D photonic crystal structures and patterns are made via periodically arrayed air holes in a thin slab, ordered periodically arrayed pillars or self‐assembled monolayers of colloidal spheres . One method of exploiting 2D photonic crystals to enhance luminescence in the vertical direction is by placing a light‐emitting layer under the 2D photonic crystal (with or without contact with the 2D photonic crystals) .…”
Section: Manipulating Luminescence By 2d Photonic Crystalsmentioning
confidence: 99%
“…In addition to 2D slabs, Ko et al coated 2D photonic crystals of monolayer polystyrene (PS) nanospheres on sputtered SrGa 2 S 4 :Eu 2+ luminescent films ( Figure ). They found that the emission and excitation intensities of the sample were greatly enhanced.…”
Section: Manipulating Luminescence By 2d Photonic Crystalsmentioning
confidence: 99%
See 1 more Smart Citation